2012
DOI: 10.1016/j.devcel.2011.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanoresponsive Cadherin-Keratin Complex Directs Polarized Protrusive Behavior and Collective Cell Migration

Abstract: Summary Collective cell migration requires maintenance of adhesive contacts between adjacent cells, coordination of polarized cell protrusions, and generation of propulsive traction forces. We demonstrate that mechanical force applied locally to C-cadherins on single Xenopus mesendoderm cells is sufficient to induce polarized cell protrusion and persistent migration typical of individual cells within a collectively migrating tissue. Local tension on cadherin adhesions induces reorganization of the keratin inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
373
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(416 citation statements)
references
References 55 publications
(79 reference statements)
26
373
1
2
Order By: Relevance
“…Recent studies have reported that cadherins transmit actomyosingenerated forces to the extracellular environment (32,33). External forces applied to cells through cadherins reveal a mechanical coupling between the membrane and the cytoskeleton that requires the cadherin cytoplasmic domain (24) and may cause changes in cellular mechanical properties or protrusive activity (25,26). Conformational changes in α-catenin and/or the recruitment of cytoskeleton-binding proteins to sites of cadherin-mediated adhesion may be involved (17,18,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have reported that cadherins transmit actomyosingenerated forces to the extracellular environment (32,33). External forces applied to cells through cadherins reveal a mechanical coupling between the membrane and the cytoskeleton that requires the cadherin cytoplasmic domain (24) and may cause changes in cellular mechanical properties or protrusive activity (25,26). Conformational changes in α-catenin and/or the recruitment of cytoskeleton-binding proteins to sites of cadherin-mediated adhesion may be involved (17,18,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that low levels of αE-catenin and actomyosin activity suffice to exert some tension on E-cadherin after drug treatment and/or protein depletion. In addition, E-cadherin may interact with intermediate filaments through desmosomal linker proteins (22,23,26,53). Intermediate filaments might constitutively exert tension on E-cadherin or compensate for reduced αE-catenin-mediated actomyosin tension following drug treatment or αE-catenin depletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, PG/JUP recruits KIF to these junctions to reorganize and reinforce the keratin cytoskeleton. Through this sequence of events, local forces from neighboring cells mediate keratin reorganization required for coordinated cell behavior (Weber et al 2012). …”
Section: Interdependence Of Keratins and Desmosomesmentioning
confidence: 99%
“…E-cadherin is under constitutive tension at cell-cell junctions and dynamically responds to changes in tension (23). Cellular responses to exogenous tension applied directly to cadherins using functionalized beads have been studied extensively (22,24,25). However, few studies have investigated how cadherins sense and respond to changes in rigidity of cell-cell interactions.…”
mentioning
confidence: 99%